ANALYSIS OF THE INFORMATION SYSTEM FOR THE DATA COLLECTION OF RESIDENTS TOWNSMAN ASSOCIATION LEVEL - Amesanggeng P; Susanto Harianto; Riki Riki; Angelina Lasut (LPPM STMIK Pringsewu, 2020)
It starts with the development of technology over time. The population continues to increase in each area, encouraging urban villages and community organizations to continue to innovate to reach convenience and use existing technology. Technologies that can comprehensively collect data and reach every citizen will resolve changes in data over time. The survey that the author conducted was in the village of Cimone Jaya. The survey found that the work on the Family Card was done manually, in which the role of urban civic associations is very vital. Old / new residents who will report must obtain approval from the local city to apply for a family card by submitting the required documents; then, it will be processed to the district stage. the district will print the family card. Through the proposed program, each head of household can register his family card online. Of course, residents can update the data, and the updated data will be approved by the local city association if the data entered is valid. This program is also able to provide invitations to every citizen and news related to the local area. This program may still have many shortcomings and still needs a lot of improvement, but this will make it easier for residents and municipal community associations to go to the sub-district